The hospital costs of complications following colonic resection surgery: A retrospective cohort study. (June 2020) - Louis, Maleck; Johnston, Samuel A.; Churilov, Leonid; Ma, Ronald; Marhoon, Nada; Burgess, Adele; Christophi, Chris; Weinberg, Laurence
Abstract: Background: Colonic resection is a common surgical procedure associated with a high rate of postoperative complications. The aim of this observational study is to estimate the in-hospital costs of complications and to identify perioperative variables associated with complication development following colon resection surgery. Materials and methods: We conducted a single-centre cohort study with retrospective data collection of 487 patients undergoing colonic resection surgery between 2013 and 2018. Postoperative complications were graded according to the Clavien-Dindo classification system. In-hospital cost of index admission is reported in 2019 United States Dollars. Regression modelling was used to investigate the relationship of a priori selected perioperative variables and presence of complications and costs. Results: Overall complication prevalence was 69.6% (95%CI:65.5%–73.7%). Median [interquartile range] cost of patients with postoperative complications was significantly increased as compared to patients without complications (17, 963 [13, 533:25, 178] vs 12, 578 [10, 196:16, 140]; p < 0.0001). Clavien-Dindo Grade I, II, III and IV complications increased costs by 15.8%, 36.8%, 169.4% and 240.1% respectively (p < 0.0001). Presence of complications was significantly associated with Charlson Comorbidity Index (Odds ratio (OR) per 1-unit increase: 1.09; 95%CI:1.02 to 1.17), preoperative albumin levels (OR per 1-unit increase: 0.94; 95%CI:0.90 to 0.98) and open as compared to laparoscopic resection (OR: 2.41; 95%CI:1.32 to 4.42). Conclusions: There is a high prevalence of complications following colonic resection surgery. Postoperative complications, including minor complications (Clavien-Dindo Grade I-II), were associated with a significant increase in hospital costs and are a key target for cost containment strategies. Graphical abstract: Image 1 Highlights: Almost 7 out of every 10 patients experienced one or more complications. Most complications were minor (Clavien-Dindo grade I-II). Minor complications significantly increased costs by over 20%. Major complications resulted in an exponential increase in costs and length of stay. Charlson Comorbidity Index and hypoalbuminemia are associated with complications.